2018
DOI: 10.1083/jcb.201712122
|View full text |Cite
|
Sign up to set email alerts
|

Nuclear dynamics of the Set1C subunit Spp1 prepares meiotic recombination sites for break formation

Abstract: Spp1 is the H3K4me3 reader subunit of the Set1 complex (COMPASS/Set1C) that contributes to the mechanism by which meiotic DNA break sites are mechanistically selected. We previously proposed a model in which Spp1 interacts with H3K4me3 and the chromosome axis protein Mer2 that leads to DSB formation. Here we show that spatial interactions of Spp1 and Mer2 occur independently of Set1C. Spp1 exhibits dynamic chromatin binding features during meiosis, with many de novo appearing and disappearing binding sites. Sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
19
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 63 publications
0
19
0
Order By: Relevance
“…Set1 complex) and Spp1's interaction with Mer2 is mutually exclusive with the remainder of the COMPASS complex 14 . Furthemore, Spp1 associated with Mer2 has a longer residence time on nucleosomes when compared with Spp1 when part of COMPASS 15 residues 140-256 of Mer2 12,13 which we from now on refer to as Mer2 "core" ( Figure 1B). We measured the molecular mass of Mer2 core by size exclusion chromatography coupled to multi-angle light scattering (SEC-MALS) and concluded that the Mer2 core is a tetramer ( Figure 1D), consistent with recently published data 17 .…”
Section: Introductionmentioning
confidence: 97%
“…Set1 complex) and Spp1's interaction with Mer2 is mutually exclusive with the remainder of the COMPASS complex 14 . Furthemore, Spp1 associated with Mer2 has a longer residence time on nucleosomes when compared with Spp1 when part of COMPASS 15 residues 140-256 of Mer2 12,13 which we from now on refer to as Mer2 "core" ( Figure 1B). We measured the molecular mass of Mer2 core by size exclusion chromatography coupled to multi-angle light scattering (SEC-MALS) and concluded that the Mer2 core is a tetramer ( Figure 1D), consistent with recently published data 17 .…”
Section: Introductionmentioning
confidence: 97%
“…For this reason, Spp1 can be found both around actively transcribed genes and in chromosome axial sites, with independence from Set1 [81]. Furthermore, set1∆ strains display a general reduction in most DSBs, which has been seen to correlate with H3K4me3 levels [82,83]. This particular strain has also been reported to present a synthetic defect with Rec114 of the RRM subcomplex [84].…”
Section: Int J Mol Sci 2020 21 X 6 Of 21mentioning
confidence: 94%
“…Indeed, Spp1 protein has been identified as a molecule that mediates the association of the loops with the axis [6,8]. Spp1, although it is a component of COMPASS, binds to the meiotic chromosome axes independently of COMPASS [23,24], and tethers H3K4me-enriched loop regions to the axis through its PHD finger, a conserved binding domain for H3K4 methylation [6,8]. Importantly, Spp1 binds to Mer2 for DSB formation on the axis [6,8].…”
Section: Introductionmentioning
confidence: 99%